2006
DOI: 10.1079/bjn20061826
|View full text |Cite
|
Sign up to set email alerts
|

Taurine status and response to intravenous taurine supplementation in adults with short-bowel syndrome undergoing long-term parenteral nutrition: a pilot study

Abstract: Taurine deficiency in patients on long-term parenteral nutrition may be involved in cholestasis. We aimed to assess plasma taurine and tauro-conjugated bile acids in adults with short-bowel syndrome and their response to intravenous taurine. Thirty-two adult patients, who had been on taurine-free parenteral nutrition for a mean of 59 (SE 14) months for short-bowel syndrome, were studied retrospectively. In a second study, a subgroup of ten patients with chronic cholestasis received taurine-enriched (6·0 (SE 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
(34 reference statements)
1
19
0
1
Order By: Relevance
“…Taurine supplementation in enteral nutrition has been studied in premature neonates without any conclusive effect on growth rate, morbidity and mortality, similar to the one trial of taurine added to parenteral nutrition in this setting, according to a Cochrane report [58]. One observational study suggested that taurine supplementation of parenteral nutrition may decrease the occurrence of parenteral nutrition-associated cholestasis in neonates [59], but a small pilot study failed to reproduce this effect in adults requiring long-term parenteral nutrition for short-bowel syndrome [60]. …”
Section: Taurinementioning
confidence: 93%
“…Taurine supplementation in enteral nutrition has been studied in premature neonates without any conclusive effect on growth rate, morbidity and mortality, similar to the one trial of taurine added to parenteral nutrition in this setting, according to a Cochrane report [58]. One observational study suggested that taurine supplementation of parenteral nutrition may decrease the occurrence of parenteral nutrition-associated cholestasis in neonates [59], but a small pilot study failed to reproduce this effect in adults requiring long-term parenteral nutrition for short-bowel syndrome [60]. …”
Section: Taurinementioning
confidence: 93%
“…Taurine deficiency in neonates is associated with cholestatic liver disease31 and this can be prevented by parenteral taurine supplementation 32. Plasma and biliary taurine concentrations are also low in adults with a short bowel33 and supplementation may improve plasma taurine but not biliary taurine concentrations 33. Intervention studies have not demonstrated a significant benefit of parenteral taurine in adults.…”
Section: Aetiology Of Ifaldmentioning
confidence: 99%
“…Multivariate analysis of data collected as part of a larger multicentre trial suggests that parenteral taurine reduces the incidence of cholestasis in severely premature infants and those with necrotising enterocolitis 32. There is considerably less evidence of a benefit of taurine supplementation in adults, with a reduction in aspartate aminotransferase levels being reported in a single small study of adults receiving long term PN 33. Choline supplementation in adults has been shown to be associated with a reduction in hepatic steatosis and improvements in LFTs 29.…”
Section: Management Of Ifaldmentioning
confidence: 99%
“…La taurine a longtemps été considé-rée avec mépris comme un « cul-de-sac » métabolique : c'est un « déchet » du catabolisme de la cystéine, elle a un turnover très lent [31] et est confinée dans le milieu intracellulaire de la plupart des tissus. Son rôle « traditionnel » est la conjugaison des sels biliaires qui sont excrétés par le foie, puis réabsorbés dans l'iléon (cycle entérohépatique), La taurine pourrait bien être un acide aminé essentiel dans le syndrome de grêle court : en effet, sa concentration chute chez les patients ayant subi une résection iléale, du fait de la perte de sels biliaires tauroconjugués induite par la rupture du cycle entérohépatique, et la concentration plasmatique de taurine est corrélée à la longueur de grêle résiduel [32].…”
Section: La Taurine Sulfoacide Conditionnellement Essentielunclassified